Engineering Research Progress of Electrochemical Microreaction Technology—A Novel Method for Electrosynthesis of Organic Chemicals - Siyuan Zheng; Junyu Yan; Kai Wang (Engineering, 2021)
Electrochemical methods are environmentally friendly and have unique advantages in the synthesis of organic chemicals. However, their implementation is limited due to the complex transport problems posed by traditional electrochemical reactors. Recently, the application of microreaction technology in electrosynthesis studies has reduced the transport distance of ions and increased the specific surface area of electrodes, leading to efficient, successive, and easily scaled-up electrosynthesis technologies. In this review article, engineering advantages of using microchannels in electrosynthesis are discussed from process enhancement perspective. Flow patterns and mass transfer behaviors in recently reported electrochemical microreactors are analyzed, and prototypes for the reactor scale-up are reviewed. As a relatively new research area, many scientific rules and engineering features of electrosynthesis in microreactors require elucidation. Potential research foci, considered crucial for the development of novel electrosynthesis technology, are therefore proposed.